2015
DOI: 10.18632/oncotarget.4822
|View full text |Cite
|
Sign up to set email alerts
|

A novel small-molecule IAP antagonist, AZD5582, draws Mcl-1 down-regulation for induction of apoptosis through targeting of cIAP1 and XIAP in human pancreatic cancer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Our top goal in this study was to find out whether FL118 alone or in combination with common pancreatic cancer chemotherapeutic drugs used in the clinic could overcome treatment-resistance in pancreatic cancer. The basis for this potential, and the initiation of this study is that upregulation of antiapoptotic proteins, survivin [ 31 38 ], Mcl-1 [ 39 47 ], XIAP [ 35 , 36 , 38 , 44 , 48 55 ], and cIPA2 [ 55 ] are strongly involved in pancreatic cancer resistance, and that FL118 has been found to inhibit such gene expression in CRC and head-&-neck tumors [ 9 ]. Based on the known mechanisms of action (MOA) and other characteristics of FL118 [ 9 ], we first determined the effects of FL118 on the expression of both antiapoptotic and proapoptotic proteins in drug-resistant pancreatic cancer cells (PANC1, MIA PaCa-2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our top goal in this study was to find out whether FL118 alone or in combination with common pancreatic cancer chemotherapeutic drugs used in the clinic could overcome treatment-resistance in pancreatic cancer. The basis for this potential, and the initiation of this study is that upregulation of antiapoptotic proteins, survivin [ 31 38 ], Mcl-1 [ 39 47 ], XIAP [ 35 , 36 , 38 , 44 , 48 55 ], and cIPA2 [ 55 ] are strongly involved in pancreatic cancer resistance, and that FL118 has been found to inhibit such gene expression in CRC and head-&-neck tumors [ 9 ]. Based on the known mechanisms of action (MOA) and other characteristics of FL118 [ 9 ], we first determined the effects of FL118 on the expression of both antiapoptotic and proapoptotic proteins in drug-resistant pancreatic cancer cells (PANC1, MIA PaCa-2).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that FL118 may have high efficacy to inhibit both tumor cell proliferation and latent cancer stem cells for effectively eliminating pancreatic cancer in the condition more closely to the clinical practice situation. This is highly possible, because survivin [ 31 38 ], Mcl-1 [ 39 47 ], XIAP [ 35 , 36 , 38 , 44 , 48 55 ], and cIPA2 [ 55 ] play critical roles in pancreatic cancer resistance to treatment, and it is also known that survivin [ 56 – 69 ], Mcl-1 [ 70 , 71 ] and XIAP [ 54 ] are involved in latent CSC drug resistance and function. Furthermore, it is well documented that ABCG2 as a critical efflux pump protein plays a vital role in maintaining viability of latent stem-like cancer cells [ 23 29 ], and the increase of ABCG2 [ 13 17 ], Pgp [ 18 21 ] expression is important for pancreatic cancer resistance to commonly used pancreatic cancer drugs in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moon et al have shown that the novel small-molecule ZAD5582 promoted TNF-α-induced apoptosis through targeting cIAP1 and XIAP in human pancreatic cancer cells [ 156 ]. AEG35156, a novel second-generation antisense oligonucleotide directed towards XIAP, increased sensitization of pancreatic carcinoma cells to TRAIL–mediated apoptosis as a single agent and was capable of inducing complete tumor regression when combined with taxanes in three human cancer xenograft models (prostate, colon, and lung) [ 157 ].…”
Section: Anti-apoptotic Mechanisms In Resistance To Chemotherapymentioning
confidence: 99%
“…The inhibitors of the apoptosis protein (IAP) family, which is characterized by 1–3 copies of Baculoviral IAP Repeat (BIR) domain, has been proved to play functional roles in cancer cell apoptosis [ 5 7 ]. High levels of IAP are observed in various cancers, such as glioblastoma and pancreatic cancer [ 8 , 9 ]. It has been reported that the IAP family can regulate cell survival via binding to the pro-apoptotic factors in tumors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%